2013
DOI: 10.3945/ajcn.112.050013
|View full text |Cite
|
Sign up to set email alerts
|

Correcting vitamin D insufficiency improves insulin sensitivity in obese adolescents: a randomized controlled trial

Abstract: The correction of poor vitamin D status through dietary supplementation may be an effective addition to the standard treatment of obesity and its associated insulin resistance. This trial was registered at clinicaltrials.gov as NCT00994396.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
254
2
12

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 282 publications
(280 citation statements)
references
References 46 publications
12
254
2
12
Order By: Relevance
“…Korean girls with low VD levels could be at increased risk for metabolic disorders. The study supports the favorable effects of vitamin D supplementation on reducing insulin resistance [34][35][36]. A lower VD level could be a risk factor for developing insulin resistance and type 2 diabetes in the obese population.…”
Section: Discussionsupporting
confidence: 55%
“…Korean girls with low VD levels could be at increased risk for metabolic disorders. The study supports the favorable effects of vitamin D supplementation on reducing insulin resistance [34][35][36]. A lower VD level could be a risk factor for developing insulin resistance and type 2 diabetes in the obese population.…”
Section: Discussionsupporting
confidence: 55%
“…Currently, the best available inflammatory biomarker is CRP, an acute phase reactant that is a reliable, independent predictor of the risk of myocardial infarction, stroke and cardiovascular death (111) . Clinical trials of vitamin D supplementation show inconsistent results regarding an effect on CRP concentrations: most report no effect (77,80,97,(112)(113)(114)(115)(116) , whereas some show reductions in CRP concentrations (74,117,118) . Some trials have measured highsensitivity CRP (hsCRP), which can detect low-grade inflammation.…”
Section: Inflammationmentioning
confidence: 99%
“…A limitation of this study is thus the unavailability of measurements for vitamin D-binding protein and IR. Some authors have suggested a possible beneficial effect of vitamin D supplementation on IR or other parameters of glucose metabolism [29,30], although others disagree [31][32][33][34]. It is also possible that other metabolic pathways [35], independent of insulin action, link visceral adipose tissue and lipid profile with 25(OH)vitamin D. Therefore, it has been suggested that the hypertriglyceridemia associated with vitamin D deficiency may be a consequence of a direct effect of vitamin D itself on lipoprotein-lipase activity [7].…”
Section: Discussionmentioning
confidence: 99%